Fear of COVID-19 scale: Psychometric characteristics, reliability and validity in the Israeli population. (July 2020) - Tzur Bitan, Dana; Grossman-Giron, Ariella; Bloch, Yuval; Mayer, Yael; Shiffman, Noga; Mendlovic, Shlomo
Highlights: The COVID-19 pandemic is expected to lead to broad psychological effects, which should be considered when performing studies assessing mental health. Only a few studies have thus far have utilized validated scales to assess the influence of the pandemic on the population's mental health, partially due to the lack of knowledge regarding their psychometric properties. The Fear of COVID-19 scale (FCV-19S) is a recently developed scale to assess different aspects of the fear of the pandemic. When evaluating the psychometric properties of the scale in a large normative sample ( n  = 639) of participants in Israel, the scale showed good internal reliability and demonstrated association with stress, anxiety, and depression. These results indicate that the scale can be utilized in studies assessing the effects of the pandemic on the population's mental health. Abstract: Mental health clinicians worldwide have been expressing concerns regarding the broad psychological effects of the COVID-19 pandemic. Nonetheless, only a few studies have thus far evaluated the degree of fear of COVID-19, partially due to the lack of validated measures. In this study we evaluated the psychometric properties of the Hebrew version of the Fear of COVID-19 scale (FCV-19S), recently developed to assess different aspects of the fear of the pandemic, in a normative population of participants in Israel. Participants ( n  = 639) were asked to complete the FCV-19S scale, as well as to report anxiety, depression, and stress levels using validated scales. The results a unidimensional factor structure of the FCV-19S which explained 53.71% of the variance. When forcing a two-factor structure model, the analysis revealed two factors pertaining to emotional fear reactions and symptomatic expressions of fear. Gender, sociodemographic status, chronic illness, being in an at-risk group, and having a family member dying of COVID-19 were positively associated with fear of COVID-19. The measure was associated with anxiety, stress and depression. These results suggest that the FCV-19S has good psychometric properties, and can be utilized in studies assessing the effects of the pandemic on the population's mental health.